RSVP extensions for real-time services in wireless mobile networks. - Moon, B.
Currently, the RSVP model, which is efficient resource reservation in the fixed endpoints, becomes invalid under host mobility. We investigate the problems of standard RSVP in providing real-time services in wireless mobile networks. We also observe carefully how to interoperate IntServ services over DiffServ networks, and how to map IntServ QoS parameters into a wireless link. We then identify the advantages and drawbacks of the existing RSVP proposals to support QoS under both micromobility and macromobility. We finally propose a dynamic resource allocation scheme for reducing service disruption of real-time applications due to frequent mobility of a host
Keywords: IntServ QoS parameters; Internet; RSVP extensions; Dynamic resource allocation; Host mobility; Macromobility; Micromobility; Real-time applications; Real-time services; Service disruption reduction; Wireless link; Wireless mobile networks